PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS PROYEK MELALUI LITERASI DIGITAL PADA MATA PELAJARAN IPAS KELAS IV SD - Siti Nurhaliza; Kiki Aryaningrum; Adrianus Dedy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop project-based augmented reality learning media through digital literacy in the subject of science for grade IV elementary school that is valid and practical. This study uses the type of research and development R&D (Research and Development) with validation by material experts obtaining a value of 83.3%, media experts obtaining a value of 86% and by linguists scored 84.6%. Furthermore, the practitioner stage is carried out through the One To One test, small groups (Small group), the population taken as many as 5 people for One To One obtained a value of 92%. Then 15 people for the small group obtained a value of 92.4%. Data were obtained through interviews, documentation and distributed questionnaires. The data analysis techniques tested were the validity and practicality of project-based augmented reality learning media through digital literacy in the subject of science for grade IV elementary school. The results of the study indicate that project-based augmented reality learning media through digital literacy in the subject of science for grade IV elementary school has met the criteria for validity and practicality for use in the learning process